A Facile "Green" Route for Scalable Batch Production and Continuous Synthesis of Zirconium MOFs. Issue 27 (16th June 2016) - Reinsch, Helge; Waitschat, Steve; Chavan, Sachin M.; Lillerud, Karl Petter; Stock, Norbert
Abstract : Considering the requirements for the commercial production of metal–organic frameworks (MOFs), we investigated the aqueous synthesis of zirconium MOFs. A highly versatile route was identified employing ZrOCl2 · 8H2 O, H2 O, acetic acid and the respective linker molecule as starting materials. These synthesis conditions are suitable to obtain zirconium MOFs with different topologies like UiO‐66‐(OH)2, zirconium fumarate, zirconium mesaconate, DUT‐67 or MOF‐808 with synthesis times of 1 to 5 h under microwave irradiation. The scalability of the synthesis of zirconium fumarate was demonstrated at multigram scale under reflux conditions using conventional dielectric heating. To ease the recovery of this MOF which bypasses filter paper as a pure product, we identified sodium polyacrylate as a suitable additive to induce aggregation of the particles. Moreover, a custom‐made prototype flow reactor was developed which allows for the continuous synthesis of zirconium fumarate and UiO‐66‐NH2 starting from a slurry of the starting materials. The commonly employed toxic organic solvents needed for activation/purification of the MOFs could be successfully replaced by a basic aqueous solution. Abstract : A "green" preparative route for the synthesis of zirconium MOFs with diverse topologies was developed. This allows the synthesis of multigram amounts in batch reactions or under continuous flow conditions.